2017
DOI: 10.3390/inventions2030015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cutting Speed on Subsurface Damage Morphology and Distribution in Ground Fused Silica

Abstract: Abstract:In optical fabrication, brittle-hard materials are used for numerous applications. Especially for high-performance optics for laser or lithography applications, a complex and consistent production chain is necessary to account for the material properties. Particularly in pre-processing, e.g., for shaping optical components, brittle material behavior is dominant which leads to a rough surface layer with cracks that reach far below the surface. This so called subsurface damage (SSD) needs to be removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…), dynamic stiffness of the grinding machine, and grinding parameters can all influence the level of subsurface damage. 13, 14 Figure 5 shows the comparison of subsurface damage of ground RB-SiC by conventional grinding and that by LAG at the laser power of 80 W. Very small micro-cracks were observed underneath the ground surface in a layer with depth 1.84 µm in conventional grinding with a depth of cut of 5 µm. The depth of damage was limited by the compliance provided by the resin-bonded grinding wheel.…”
Section: Resultsmentioning
confidence: 99%
“…), dynamic stiffness of the grinding machine, and grinding parameters can all influence the level of subsurface damage. 13, 14 Figure 5 shows the comparison of subsurface damage of ground RB-SiC by conventional grinding and that by LAG at the laser power of 80 W. Very small micro-cracks were observed underneath the ground surface in a layer with depth 1.84 µm in conventional grinding with a depth of cut of 5 µm. The depth of damage was limited by the compliance provided by the resin-bonded grinding wheel.…”
Section: Resultsmentioning
confidence: 99%
“…They found that surface roughness could be reduced by increasing the wheel speed due to the increase of ductile grinding probability which benefited from the reduced chip thickness. Schnurbusch et al [4] investigated the influences of cutting speed on grinding forces, surface roughness and subsurface damage in the grinding process of fused silica. They found that the changing trend of grinding forces was different from the surface roughness and subsurface damage depth, and they attributed the increase of grinding force with grinding speed to the higher rate of ductile material removal.…”
Section: Introductionmentioning
confidence: 99%